The Controversy of Online Learning in English Language Education - Astuti, Puji; Faruk, Ahmad (Institut Agama Islam Negeri Palopo, 2025)
This study aims to examine the controversy of online learning in English language education, highlighting its impact on accessibility, student engagement, and communication skills development. The focus of the study is on an in-depth analysis of the advantages and disadvantages of online learning at Mukhtar Syafaat, an educational institution that has implemented this method intensively post-pandemic. The research method uses a mixed approach with interviews, observations, and documentation, which aims to obtain qualitative and quantitative data that support a more comprehensive understanding. The results of the study indicate that online learning provides flexibility and ease of access, but faces significant challenges in increasing student engagement and social interaction. The lack of interactive pedagogical design and minimal support for collaborative technology are the main causes of dysfunction in several aspects of learning. However, with better technology integration and a collaborative approach, online learning has great potential to support inclusive and adaptive education. The contribution of this study is to provide a new perspective in the development of more effective online learning methods, especially for English language education. This study is also an important reference for educators, policy makers, and technology developers in creating online learning systems that support the development of language skills holistically.